Imitating Job: A Micro-Ethnographic Comment - Pfoh, Emanuel Oreste (2018)
This brief contribution notes the similarities between an ethnographically attested model of behaviour and the key theme in the biblical book of Job. It also aims to provide an explanation for the permanence of a Jobian model of behavior after more than two millennia in Southern Levant.